Are there patients missing from community heart failure registers? An audit of clinical practice. (February 2019) - Cuthbert, Joseph J; Gopal, Jayanthi; Crundall-Goode, Amanda; Clark, Andrew L
Background: General practitioners in the UK are financially incentivised, via the Quality Outcomes Framework, to maintain a record of all patients at their practice with heart failure and manage them appropriately. The prevalence of heart failure recorded in primary care registers (0.7–1.0%) is less than reported in epidemiological studies (3–5%). Using an audit of clinical practice, we set out to investigate if there are patients 'missing' from primary care heart failure registers and what the underlying mechanisms might be. Design: The design of this study was as an audit of clinical practice at a UK general practice ( n  = 9390). Methods: Audit software (ENHANCE-HF) was used to identify patients who may have heart failure via a series of hierarchical searches of electronic records. Heart failure was then confirmed or excluded based on the electronic records by a heart failure specialist nurse and patients added to the register. Outcome data for patients without heart failure was collected after two years. Results: Heart failure prevalence was 0.63% at baseline and 1.12% after the audit. Inaccurate coding accounted for the majority of missing patients. Amongst patients without heart failure who were taking a loop diuretic, the rate of incident heart failure was 13% and the rate of death or hospitalization with heart failure was 25% respectively during two-year follow-up. Conclusion: There are many patients missing from community heart failure registers which may detriment patient outcome and practice income. Patients without heart failure who take loop diuretics are at high risk of heart failure-related events.